HUBUNGAN BEBAN KERJA MENTAL TERHADAP PEMBERIAN ASI EKSKLUSIF PADA IBU BEKERJA DI WILAYAH KERJA PUSKESMAS KARANGJATI - Hevita Windryani Putri Waluyo; Ekawati Ekawati; Baju Widjasena; Hanifa Maher Denny (Jurnal Kesehatan Masyarakat, 2019)
Exclusive breastfeeding is the only breastmilk that is given to the infants without other liquids nor solids. Working mothers who are married and bearing a baby have an obligation to breastfeed their babies. The obligation to breastfeed and have a working make mothers get a mental workload. The purpose of this study was to analyze the relationship between mental workload and exclusive breastfeeding on working mothers in the working area of the Karangjati Health Center, Ngawi District. This research was a quantitative study using cross-sectional approach. The population of this study was 71 working mothers who were selected to be 62 samples and made the inclusion criteria. The interviews were conducted using NASA-TLX questionnaires. Data was analyzed using Chi-square test. A significant result was found there was association between mental workload and exclusive breastfeeding with p-value 0,022 with α=0,05.